2009
DOI: 10.1111/j.1469-8986.2008.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological outcomes of health qigong for chronic conditions: A systematic review

Abstract: We aimed to unravel the clinical benefits and the plausible underlying psychophysiological mechanism based on available randomized controlled trials (RCTs). Meta-analysis of 26 RCTs shortlisted from electronic databases from 1997 to 2006 shows that qigong had some effects on increasing the numbers of white blood cells and lymphocytes, stroke volume, peak early transmitral filling velocity, peak late transmitral filling velocity, forced vital capacity, and forced expiratory volume, and, conversely, lowering of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 47 publications
(72 reference statements)
1
78
0
Order By: Relevance
“…[42][43][44] Moreover, the review of HQG practice among clinical populations suggests that the psychophysiologic outcomes are systemic in nature, which include enhancing circulation, improving ventilation, and strengthening immune responses. 45 These are in line with the current concepts of the development of complementary and alternative medicine. 46 On the other hand, the effect of systemic inflammation on the pathophysiology and morbidity of COPD has attracted increasing concerns.…”
mentioning
confidence: 53%
“…[42][43][44] Moreover, the review of HQG practice among clinical populations suggests that the psychophysiologic outcomes are systemic in nature, which include enhancing circulation, improving ventilation, and strengthening immune responses. 45 These are in line with the current concepts of the development of complementary and alternative medicine. 46 On the other hand, the effect of systemic inflammation on the pathophysiology and morbidity of COPD has attracted increasing concerns.…”
mentioning
confidence: 53%
“…The choice of whether to conduct qualitative or quantitative synthesis is not always an obvious one. For example, two SRs examined the effectiveness of qigong for chronic conditions in the elderly [37, 38]. Given the similarity of the two SRs, one would expect both to have used the same synthesis method.…”
Section: Discussionmentioning
confidence: 99%
“…42 The results regarding clinical respiratory parameters may have implications for the design of future trials, because, although a commonly used outcome measure in clinical practice, these health parameters vary widely for people with CF; the broader impact of meditative movement on quality of life, well-being, and psychosocial outcomes may be more appropriate to capture in studies of meditative movement. 78,79 Although the studies included indicate that it is unlikely that meditative movement, compared with no treatment, affects V O 2 or maximum aerobic capacity, a previous metaanalysis of experimental studies of tai chi found a small effect size for V O 2 (0.33, 95% CI 0.41-1.07). 27 Most of the studies compared the intervention with either standard care or no treatment, which limits the interpretation of the evidence regarding the specific effects of meditative movement over and above extra attention.…”
Section: Discussionmentioning
confidence: 99%
“…27 This review has found that the evidence for meditative movement for people with CF is non-existent; however, evidence suggests that meditative movement has both physical and psychological benefits for people with chronic health conditions. 78,79 The possible benefit of meditative movement for CF may not be respiratory function, but rather as a holistic intervention incorporating physical, psychological, social, and philosophical aspects, 82 and in providing self-management, gentle exercise, flexibility, posture, mindfulness, and improved quality of life. Treatment for people with CF is complex and includes daily chest physiotherapy, exercise, supplements to avoid malnutrition, and oral and nebulized antibiotics (predominantly self-administered), resulting in high burden for patients.…”
Section: Clinical/practical Implicationsmentioning
confidence: 99%